Masturbation and Pornography Use Among Coupled Heterosexual Men With Decreased Sexual Desire: How Many Roles of Masturbation? - Carvalheira, Ana; Traeen, Bente; Štulhofer, Aleksandar (2014)
The relation between masturbation and sexual desire has not been systematically studied. The present study assessed the association between masturbation and pornography use and the predictors and correlates of frequent masturbation (several times a week or more often) among coupled heterosexual men who reported decreased sexual desire. Analyses were carried out on a subset of 596 men with decreased sexual desire (mean age = 40.2 years) who were recruited as part of a large online study on male sexual health in 3 European countries. A majority of the participants (67%) reported masturbating at least once a week. Among men who masturbated frequently, 70% used pornography at least once a week. A multivariate assessment showed that sexual boredom, frequent pornography use, and low relationship intimacy significantly increased the odds of reporting frequent masturbation among coupled men with decreased sexual desire. These findings point to a pattern of pornography-related masturbation that can be dissociated from partnered sexual desire and can fulfill diverse purposes. Clinical implications include the importance of exploring specific patterns of masturbation and pornography use in the evaluation of coupled men with decreased sexual desire.
Projekt MZOS
ENG